The effect of reactive oxygen species on respiratory complex I activity in liposomes - Eisermann,J; Liang,Y; Wright,JJ; Clifford,E; Wilton-Ely,JDET; Kuimova,M; Roessler,M (Chemistry: A European Journal, 2024)
Respiratory complex I (R-CI) is an essential enzyme in the mitochondrial electron transport chain but also a major source of reactive oxygen species (ROS), which are implicated in neurodegenerative diseases and ageing. While the mechanism of ROS production by R-CI is well-established, the feedback of ROS on R-CI activity is poorly understood. Here, we perform EPR spectroscopy on R-CI incorporated in artificial membrane vesicles to reveal that ROS (particularly hydroxyl radicals) reduce R-CI activity by making the membrane more polar and by increasing its hydrogen bonding capability. Moreover, the mechanism that we have uncovered reveals that the feedback of ROS on R-CI activity via the membrane is transient and not permanent; lipid peroxidation is negligible for the levels of ROS generated under these conditions. Our successful use of modular proteoliposome systems in conjunction with EPR spectroscopy and other biophysical techniques is a powerful approach for investigating ROS effects on other membrane proteins.